Aplikasi Konsep Tropis pada Restoran dan Retail di Bojonegoro - Kurniawati, Dessy (Intra, 2017)
As a developing city, Bojonegoro requires innovation in commercial needs. This interior design aims to answer the problems of the community who require facilities for eating, drinking and retailing. In fact, people need a new atmosphere to relax. Therefore, the application of the concept of "Tropical Relaxation" aims to show the impression of relaxed, comfortable with a new atmosphere in the restaurant and retail. This concept also brings the natural atmosphere into the room so that the connection between the outdoor and the indoor stay in harmony. Entertainment in the form of local arts typical Bojonegoro also presented as something new to the community as an entertainment and at the same time to preserve the local culture.